The Environmental Kuznets Curve: A Survey of the Literature - Simone Borghesi (Fondazione Eni Enrico Mattei (FEEM), 1999)
In the last few years, several studies have found an inverted-U relationship between per capita income and environmental degradation. This relationship, known as the environmental Kuznets curve (EKC), suggests that environmental degradation increases in the early stages of growth, but it eventually decreases as income exceeds a threshold level. The present paper reviews both early and recent contributions on this subject, discussing whether and to what extent such a curve can be empirically observed, and the policy implications that derive from the empirical evidence
Keywords: C23; O5; Q2; Q25; Q32; 330; Environmental Kuznets Curve; Growth; Pollution